Secondary Metabolites and Antioxidant Properties of Lichens from Sicike-Cike Nature Park, North Sumatra - Putri Amelia Lubis; Etti Sartina Siregar; Isnaini Nurwahyuni (Postgraduate, University of Mataram, 2025)
This study aimed to evaluate the phytochemical composition and antioxidant activity of five lichen species Cladonia portentosa, Cladonia rapii, Letharia vulpina, Parmotrema hypotropum, and Usnea trichodea collected from Sicike-Cike Nature Park, North Sumatra, Indonesia. Methanol extracts were prepared from dried and powdered lichen samples. Qualitative phytochemical screening using specific reagents identified the presence of alkaloids, flavonoids, tannins, saponins, terpenoids/steroids, and glycosides in varying levels among the species. Antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, with IC50 values ranging from 42.3244 µg/mL to 86.7479 µg/mL. Parmotrema hypotropum demonstrated the strongest antioxidant activity (IC50 = 42.3244 µg/mL), categorized as moderate based on literature benchmarks. The strong activity is likely due to the presence of alkaloids, flavonoids, and saponins. In contrast, Usnea trichodea showed the weakest activity. These results suggest that certain lichens, especially Parmotrema hypotropum, may serve as promising sources of natural antioxidants. The findings support potential applications in pharmaceutical formulations and natural cosmetic products, particularly those targeting oxidative stress. Future studies should focus on isolating dominant compounds such as usnic acid or flavonoid derivatives and further exploring their bioactivity profiles.